Looking Beyond the Glioblastoma Mask: Is Genomics the Right Path? - Montella, Liliana; Del Gaudio, Nunzio; Bove, Guglielmo; Cuomo, Mariella; Buonaiuto, Michela; Costabile, Davide; Visconti, Roberta; Facchini, Gaetano; Altucci, Lucia; Chiariotti, Lorenzo; Della Monica, Rosa (Frontiers in Oncology, 2022)
Glioblastomas are the most frequent and malignant brain tumor hallmarked by an invariably poor prognosis. They have been classically differentiated into primary isocitrate dehydrogenase 1 or 2 (IDH1 -2) wild-type (wt) glioblastoma (GBM) and secondary IDH mutant GBM, being IDH wt GBMs commonly associated with elder age and poor prognosis. Recently, genetic analyses have been integrated with epigenetic investigations, strongly implementing typing and subtyping of brain tumors, including GBMs, and leading to the new WHO 2021 classification. GBM genomic and epigenomic profile influences evolution, resistance, and therapeutic responses. However, differently from other tumors, there is a wide gap between the refined GBM profiling and the limited therapeutic opportunities. In addition, the different oncogenes and tumor suppressor genes involved in glial cell transformation, the heterogeneous nature of cancer, and the restricted access to the blood-brain barrier have limited clinical advancements. This review will summarize the more relevant genetic alterations found in GBMs and highlight their potential role as potential therapeutic targets.